حماية رضا المستهلك في التعاقد عبر الانترنت دراسة في القانونين العراقي والفرنسي - الساعدي, جليل حسن (Journal of Legal Sciences, 2020)
This research deals with the protection of the consumer's acceptance by internet, we divided it into four sections, the first section is devoted to the concept of the consummation contract by internet. The second section was about the professional's offer by internet, while we studied in the third section the consumer's acceptance by internet, at the last section we discussed the agreement of the protection consumer's acceptance.